2011
DOI: 10.1007/s11738-011-0728-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in germinability, lipid peroxidation, and antioxidant enzyme activities in pear stock (Pyrus betulaefolia Bge.) seeds during room- and low-temperature storage

Abstract: The aim of this study was to determine if loss of germinability in Pyrus betulaefolia seeds stored at 4°C and at room temperature is associated with a loss of membrane lipid peroxidation or changes in antioxidant enzyme activities. The results indicated that germination percentage clearly decreased when seeds were stored at room temperature rather than at 4°C from 6 to 12 months. Room-temperature storage of the pear stock seed for 12 months decreased germination to 15.52%, but germination percentage was not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…The decreased PODa levels that have been observed in various seeds is associated with losses of viability and germination capacities during storage (Balešević-Tubić et al 2005 , 2011 ; Bao et al 2011 ; Chauhan et al 2011 ; Goel and Sheoran 2003 ; Scialabba et al 2002 ). In stored maize, increased temperatures in conditions of high humidity (88% RH at 25°C) lead to rapid deterioration after 3 months with decreased germination rates and abrupt decreases in scutellum PODa levels (Figure 7 c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased PODa levels that have been observed in various seeds is associated with losses of viability and germination capacities during storage (Balešević-Tubić et al 2005 , 2011 ; Bao et al 2011 ; Chauhan et al 2011 ; Goel and Sheoran 2003 ; Scialabba et al 2002 ). In stored maize, increased temperatures in conditions of high humidity (88% RH at 25°C) lead to rapid deterioration after 3 months with decreased germination rates and abrupt decreases in scutellum PODa levels (Figure 7 c).…”
Section: Discussionmentioning
confidence: 99%
“…This may compromise seed viability, for example, during storage (Goel and Sheoran 2003 ). Excessive ROS concentrations are also associated with decreased PODa in various seeds, including sunflower, soybean, pear stock, wheat, cotton and radish (Balešević-Tubić et al 2005 , 2011 ; Bao et al 2011 ; Chauhan et al 2011 Goel and Sheoran 2003 ; Scialabba et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we were unable to nd a voucher specimen of Limonium bicolor stored in any publicly available herbarium. The dried seeds were stored at 4°C for at least six months [24]. Before use, the seeds were surface-disinfected with 70% ethanol (5 min), followed by 6% (v/v) NaClO (Sigma, USA) for 17 min with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of Cu-Zn-SOD genes in tobacco seeds improved seed longevity and germination by attenuating the effects of oxidative stress produced by elongated storage conditions and harsh environmental stresses (Lee et al 2010). It was suggested that loss of seed viability with ageing is associated with a decrease in SOD activity (Lehner et al 2008;Bao et al 2011;Xia et al 2015;Sahu et al 2017b). In the present study, Cu-Zn SOD level decreased at 3°C, which is in agreement with the above results; however, it increased only at − 3°C after 12 months of storage.…”
Section: Proteins Involved In Stress Responsesmentioning
confidence: 99%